Age- and Gender-Related Differences in LDL-Cholesterol Management in Outpatients with Type 2 Diabetes Mellitus - Giuseppina Russo; Basilio Pintaudi; Carlo Giorda; Giuseppe Lucisano; Antonio Nicolucci; Maria Rosaria Cristofaro; Concetta Suraci; Maria Franca Mulas; Angela Napoli; Maria Chiara Rossi; Valeria Manicardi (International Journal of Endocrinology)
Background. Dyslipidemia contribute to the excess of coronary heart disease (CHD) risk observed in women with type 2 diabetes (T2DM). Low density lipoprotein-cholesterol (LDL-C) is the major target for CHD prevention, and T2DM women seem to reach LDL-C targets less frequently than men. Aim. To explore age- and gender-related differences in LDL-C management in a large sample of outpatients with T2DM. Results. Overall, 415.294 patients (45.3% women) from 236 diabetes centers in Italy were included. Women were older and more obese, with longer diabetes duration, higher total-cholesterol, LDL-C, and HDL-C serum levels compared to men (P<0.0001). Lipid profile was monitored in ~75% of subjects, women being monitored less frequently than men, irrespective of age. More women did not reach the LDL-C target as compared to men, particularly in the subgroup treated with lipid-lowering medications. The between-genders gap in reaching LDL-C targets increased with age and diabetes duration, favouring men in all groups. Conclusions. LDL-C management is worst in women with T2DM, who are monitored and reach targets less frequently than T2DM men. Similarly to men, they do not receive medications despite high LDL-C. These gender discrepancies increase with age and diabetes duration, exposing older women to higher CHD risk.